European electronic payments markets report 2022 - status quo analysis of psd2 and open banking - Hackl, Felix Christian Joseph (2022)
This report examines the European payment market using proprietary data on FinTech startups. Through the perspectives of various interviewees, it analyzes the impact of PSD2 and Open Banking on the payment industry and the emergence of new payments verticals. The adoption of PSD2 in 2018 and the Open Banking framework led to more competition from third-party providers, especially in the UK, and fostered financial inclusion. However, the European market is still fragmented in terms of different API standards and regulatory arbitrage opportunities within the EEA, which will need to be further regulated by a new scheme, from the European Commission in the next two years.